Short communication. Inheritance of yield, yield components and resistance to major diseases in Sesamum indicum L. - El-Bramawy, M.A.S.; Shaban, W.I. (Spanish Journal of Agricultural Research, 2008)
Field experiments were conducted over 2005 and 2006 to study the gene action associated with yield and ten yield components, as well as resistance Fusarium wilt, charcoal rot and Alternaria leaf spot, in 6 x 6 half-diallel sesame progenies (F1). Highly significant differences among the 15 F1s and their six parents were detected with respect to all the investigated traits. A preponderance of non-additive genetic variance was seen for all the studied traits, except for days to maturity and resistance to Alternaria leaf spot. Ten traits showed overdominance. Recessive alleles were predominantly involved in fruiting branches/plant, capsules/plant and single plant yield. The distribution of genes with positive and negative effects were symmetrical or nearly symmetrical with respect to 1000-seed weight, charcoal rot disease resistance, fruiting branches/plant, capsules/plant, single plant yield, and oil content. The parents possessed mostly negative genes in dominant form with respect to capsules/plant, 1000-seed weight, oil content, and resistance to charcoal rot and Alternaria leaf spot; positive genes in recessive form were observed for the rest of the studied traits. Given the gene action observed, biparental mating or diallel selective mating and heterosis breeding is suggested for the improvement of sesame.